Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Pada Donat Jeko di Kotabumi - Apriliansyah, Rizki; Putriwarganegara, Tri Lestira (Jurnal EMT KITA, 2024)
Consumer purchasing decisions are a crucial factor in a company's marketing strategy, especially in the competitive food and beverage industry. This study aims to analyze the influence of price and promotion on consumer purchasing decisions at Jeko Donuts in Kotabumi. The research employs a descriptive analysis method, collecting data through a survey involving 100 respondents. The findings reveal that, partially, the price variable has a positive and significant influence on purchasing decisions. This indicates that appropriate price adjustments can enhance consumer buying interest. Furthermore, the promotion variable also demonstrates a positive and significant influence on purchasing decisions, suggesting that innovative and attractive promotional activities can increase product appeal to consumers. Simultaneous analysis reveals that price and promotion together have a significant influence on purchasing decisions. These findings highlight the importance of combining price and promotion strategies to boost sales and product competitiveness in the market.